SOCIAL MANAGEMENT MODEL OF HOLISTIC GOVERNANCE FRAMEWORK FOR PREVENTION OF CHILD SEXUAL ABUSE - Chekkara, Aslammoideen; Kunjappan, Sony (International Journal of Research -GRANTHAALAYAH, 2022)
In a country like India, which has a child population exceeding 472 million Office of the Registrar General and Census Commissioner (2011), Child safety is given paramount importance. According to research done by the "MWCD," 53.2 percent of children examined were victims of Child Sexual Abuse (CSA), with 20.9 percent being violently assaulted Kacker et al. (2007). “The "Protection of Children from Sexual Offenses Act" (POCSO) went into force on November 14, 2012”. It conferred protective rights to the victims of CSA cases. The rationale behind the formulation of the Statute was to obliterate CSA, and also to create awareness about the severity of CSA. It is imperative to note here that POCSO works only as a legislative deterrence and deterrence alone cannot annihilate the problem. This paper suggests a Social Management Model of Holistic Governance Framework effectively done by reviewing sixteen different prevention strategies associated with the development of the child community as a constructive solution at large.